A decade of progress in liver regenerative medicine. (March 2018) - Zhang, Jingwei; Zhao, Xin; Liang, Liguo; Li, Jun; Demirci, Utkan; Wang, ShuQi
Abstract: Liver diseases can be caused by viral infection, metabolic disorder, alcohol consumption, carcinoma or injury, chronically progressing to end-stage liver disease or rapidly resulting in acute liver failure. In either situation, liver transplantation is most often sought for life saving, which is, however, significantly limited by severe shortage of organ donors. Until now, tremendous multi-disciplinary efforts have been dedicated to liver regenerative medicine, aiming at providing transplantable cells, microtissues, or bioengineered whole liver via tissue engineering, or maintaining partial liver functions via extracorporeal support. In both directions, new compatible biomaterials, stem cell sources, and bioengineering approaches have fast-forwarded liver regenerative medicine towards potential clinical applications. Another important progress in this field is the development of liver-on-a-chip technologies, which enable tissue engineering, disease modeling, and drug testing under biomimetic extracellular conditions. In this review, we aim to highlight the last decade's progress in liver regenerative medicine from liver tissue engineering, bioartificial liver devices (BAL), to liver-on-a-chip platforms, and then to present challenges ahead for further advancement.